Estudio del efecto de diferentes fuentes de fibra en la digestibilidad de nutrientes en pollos de carne criados en altura - Cruz Castillo, Bryan David (2023)
The digestibility coefficient is used to calculate the available nutrient proportion for absorption. The goal of the present investigation was to evaluate the effect of the diets of nutrient digestibility on chicken´s growth in highness. This was developed to 4 processing, and 4 experimental units respectively, also using 64 chickens of the mark Cobb 500 of 42 old days, with a range weight of 7075 g. Moreover, the completely wrong desing, treatment as T1 (control) with the inclusion of 5 % of wheat afrecho and the remainder of treatment with the inclusion of 18 % of (wheat afrecho) T2, (rice cascarilla) T3, and (palmist), T4. This was an adaptation periodo of seven days, afteward the three days were gathering the detections and writing down the chiken´s weigtht and excretes. The factors analyzed were affectuated across the method AOAC, these dates were processed in the infestat statistic packet, and the result was digestibility coefficient in vivo de MS, MO and GC obtain statistic difference (p<0,005) inside the source of inclusion, fiber in variable different. In conclusion, the inclusion of 18 % of subproducts of crop practice in the production of chickens according to a variable of digestibility coefficient of 50 % is considered admissible and as a suggestion realize a test analysis of quality control of the source materials before being cosidered as diet.